PERANCANGAN APLIKASI BERBASIS ANDROID SEBAGAI PLATFORM PENGHUBUNG UMKM DAN INFLUENCER DALAM MENDUKUNG PROMOSI DIGITAL - Arwidya Diestyana; Arief Tri Arsanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital marketing has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize technology to enhance promotional effectiveness. However, the process of finding influencers as promotional partners is still conducted manually, making it inefficient, lacking transparency, and creating difficulties for both parties in establishing collaborations. This study aims to design an Android-based application that serves as a digital platform connecting MSMEs with influencers to support digital marketing activities. The research employed the Research and Development (R&D) approach using the Waterfall development model, which consists of requirements analysis, system design, implementation, testing, and maintenance. Data were collected through literature review, observation, interviews, and questionnaires. The developed application, Arui Digital, provides features including user registration, profile management, promotion requests, real-time chat, digital payment, rating, and a blacklist system to ensure service quality. System evaluation using Black Box Testing demonstrated that all primary features functioned according to the specified requirements. The findings indicate that the application facilitates a more structured collaboration process between MSMEs and influencers, enhances transparency in promotional partnerships, accelerates communication and transaction processes, and supports reputation management through rating and blacklist features. Therefore, Arui Digital has the potential to become an effective Android-based solution for strengthening the digital promotion ecosystem of MSMEs.